“Not Your Father’s Heart”: How Healthcare Discrimination for Neurodivergent Patients Taught Me About the Human Experience - Cate Murphy (Patient Experience Journal, 2024)
It is easy to assume all patients who come into a hospital for acute crisis care have a clear understanding of how their experience will be facilitated. When a patient is neurodivergent, they cannot always agree to needed intervention. This is exacerbated by the “poor timing” of questions portrayed to impact the critical care received, sometimes irreparably. This is my story of watching my young, active partner suffer two massive heart attacks and refuse intervention because he was ashamed to admit he had not seen a doctor in over thirty years. Due to his neurodivergence, he could not process questions under pressure, held the belief he had no health insurance, and could not afford care. This is also the story of how one talented cardiothoracic surgeon listened to my partner through the ears of a patient and nothing more. My experience with the intersection of patient experience and healthcare volunteerism led me to advocating for a truly terrified human being and I realized this was not the storybook heart attack portrayed in movies or what we typically hear from our parents or grandparents. This was living, in real-time, the thought I would lose my partner because he could not cope. We are on the other side now, but I wonder what other neurodivergent patients do when they do not have someone like me. I hope my story helps providers and PX professional think through the lens of those who cannot follow the traditional expectations of emergent care.